The monstrumologist eaudiobook - Yancey, Rick (Monstrumologist, 2009)
MONSTERS ARE REAL. Will Henry is the orphan apprentice of a doctor with an unusual specialty: monstrumology, the study of monsters. When a midnight visitor brings them the body of a young girl entwined with the corpse of an Anthropophagus, it is the start of the most mysterious case of Will Henry's life. Anthropophagi are headless monsters whose razor-sharp teeth are in their stomachs—and they are supposed to be extinct in this part of the world. Now Will and the monstrumologist are in a race against time to put a stop to the plague of monsters before they kill again. "Will's intelligent diary captures their page-turning, nightmarish adventures and the constructs and evolving scientific theories of the time as well as his budding independence."—Kirkus Reviews